Secondary organic aerosol formation from camphene oxidation: measurements and modeling - Q. Li; Q. Li; J. Jiang; J. Jiang; I. K. Afreh; I. K. Afreh; K. C. Barsanti; K. C. Barsanti; D. R. Cocker III; D. R. Cocker III (Atmospheric Chemistry and Physics, 2022)
While camphene is one of the dominant monoterpenes measured in biogenic and pyrogenic emission samples, oxidation of camphene has not been well-studied in environmental chambers and very little is known about its potential to form secondary organic aerosol (SOA). The lack of chamber-derived SOA data for camphene may lead to significant uncertainties in predictions of SOA from oxidation of monoterpenes using existing parameterizations when camphene is a significant contributor to total monoterpenes. Therefore, to advance the understanding of camphene oxidation and SOA formation and to improve representation of camphene in air quality models, a series of experiments was performed in the University of California Riverside environmental chamber to explore camphene SOA mass yields and properties across a range of chemical conditions at atmospherically relevant OH concentrations. The experimental results were compared with modeling simulations obtained using two chemically detailed box models: Statewide Air Pollution Research Center (SAPRC) and Generator for Explicit Chemistry and Kinetics of Organics in the Atmosphere (GECKO-A). SOA parameterizations were derived from the chamber data using both the two-product and volatility basis set (VBS) approaches. Experiments performed with added nitrogen oxides (NOx) resulted in higher SOA mass yields (up to 64 %) than experiments performed without added NOx (up to 28 %). In addition, camphene SOA mass yields increased with SOA mass (Mo) at lower mass loadings, but a threshold was reached at higher mass loadings in which the SOA mass yields no longer increased with Mo. SAPRC modeling of the chamber studies suggested that the higher SOA mass yields at higher initial NOx levels were primarily due to higher production of peroxy radicals (RO2) and the generation of highly oxygenated organic molecules (HOMs) formed through unimolecular RO2 reactions. SAPRC predicted that in the presence of NOx, camphene RO2 reacts with NO and the resultant RO2 undergoes hydrogen (H)-shift isomerization reactions; as has been documented previously, such reactions rapidly add oxygen and lead to products with very low volatility (i.e., HOMs). The end products formed in the presence of NOx have significantly lower volatilities, and higher O : C ratios, than those formed by initial camphene RO2 reacting with hydroperoxyl radicals (HO2) or other RO2. Further analysis reveals the existence of an extreme NOx regime, wherein the SOA mass yield can be suppressed again due to high NO /<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="c6f00d13d95b9183e3e2526db4298e27"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-22-3131-2022-ie00001.svg" width="8pt" height="14pt" src="acp-22-3131-2022-ie00001.png"/></svg:svg> HO2 ratios. Moreover, particle densities were found to decrease from 1.47 to 1.30 g cm−3 as [HC]0 /<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="78c74280a32911099c6aadbec3864e34"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-22-3131-2022-ie00002.svg" width="8pt" height="14pt" src="acp-22-3131-2022-ie00002.png"/></svg:svg> [NOx]0 increased and O : C decreased. The observed differences in SOA mass yields were largely explained by the gas-phase RO2 chemistry and the competition between RO2+ HO2, RO2+ NO, RO2+ RO2, and RO2 autoxidation reactions.